2020
DOI: 10.1038/s41598-020-61189-7
|View full text |Cite
|
Sign up to set email alerts
|

Giant defect emission enhancement from ZnO nanowires through desulfurization process

Abstract: of about 5.3 meV which shows a good agreement to the ambient thermal energy at 70 K. Traditionally, ZnO:Zn with high defect emission can be created directly through the use of very high temperature processes. We have shown here that through the sulfurization/desulfurization process strong defect emission can be induced at lower temperatures with greater control over degree of defects induced. This is an important advancement, particularly in the field of earth-abundant phosphors. Experimental Details and Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…ZnO nanorods, the visible emission peak of ZnO nanoparticles/nanofibers shifted to a longer wavelength of ~ 660 nm, and NBE peak disappeared. The dominated visible emission peak in the PL in ZnO suggested that oxygen vacancy defects exist in ZnO [11,12]. However, it should be noted that the visible emission peak of ZnO nanoparticles/nanofibers was much higher than that of ZnO nanorods.…”
Section: Resultsmentioning
confidence: 96%
“…ZnO nanorods, the visible emission peak of ZnO nanoparticles/nanofibers shifted to a longer wavelength of ~ 660 nm, and NBE peak disappeared. The dominated visible emission peak in the PL in ZnO suggested that oxygen vacancy defects exist in ZnO [11,12]. However, it should be noted that the visible emission peak of ZnO nanoparticles/nanofibers was much higher than that of ZnO nanorods.…”
Section: Resultsmentioning
confidence: 96%
“…Samples A1-A3 (Figure 9a-c) and B1-B3 (Figure 9d-f) appeared slightly yellowish due to the presence of β-Zn 2 SiO 4 which was responsible for the yellow emission. Whereas the green emission was evident in samples C1-C3 (Figure 9g-i) and D1-D3 (Figure 9j-l) sintered under various holding times indicated the occupancy of α-Zn 2 SiO 4 [54]. Particularly, samples C appeared in yellowish-green.…”
Section: Optical Characterization Of the Zno-b 2 O 3 -Sio 2 (Zbs) Glamentioning
confidence: 95%
“…Zinc oxide is a crystalline inorganic material which mainly exists in the wurtzite crystal phase 81 . Zinc oxide is a commonly used support in a reactive adsorption process.…”
Section: Adsorptionmentioning
confidence: 99%
“…It was found that 13 wt % Ni on ZnO gave the highest catalytic activity. From 117 mg/L initial sulfur concentration, the processed crude oil only contains less than 0.1 mg/L sulfur content after reactive adsorption process using Ni/ZnO material 81 …”
Section: Adsorptionmentioning
confidence: 99%